Seating system for scoliosis in nonambulatory children with cerebral palsy: A randomized controlled trial - ŞANLI, GÖKTUĞ; TATAR, YAŞAR (My University, 2022)
OBJECTIVE: This study aimed to investigate the effect of an adaptive seating system on pelvic obliquity and spinal coronal/sagittal balance in children with nonambulatory cerebral palsy and scoliosis. METHODS: This was a single-blind, prospective, randomized interventional study. Nonambulatory children aged 6???15 years with cerebral palsy and scoliosis were included. The seating system was used for 4 h/day, and exercises were performed 3 days/week for 12 weeks. The Cobb angle, spinopelvic parameters, pelvic obliquity, Reimer???s migration index, and Sitting Assessment Scale were measured before and after treatments. RESULTS: A total of 29 participants were randomized into two groups, namely, the seating system+exercise group (SSE-group; n=15) and the exercise group (E-group; n=14). There was no significant change in Cobb angle and Reimer???s migration index for both hips in SSE-group, but there was a significant increase in E-group (p=0.002, 0.049, and 0.003, respectively). The sagittal vertical axis, pelvic incidence, and pelvic obliquity decreased in SSE-group. However, there was no difference in the other sagittal parameters and Sitting Assessment Scale-total scores among groups. CONCLUSION: The adaptive seating system was found to be superior in reducing the progression of Cobb angle and hip subluxation/dislocation, decreasing pelvic obliquity, and improving the sagittal balance of the spine/pelvis compared with exercise therapy.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Cerebral palsy; Sitting; Scoliosis; Spine; Pelvis; SPINOPELVIC PARAMETERS; PELVIC INCIDENCE; MANAGEMENT; CLASSIFICATION; Cerebral palsy; Sitting; Scoliosis; Spine; Pelvis